2001
DOI: 10.1152/ajplung.2001.281.3.l639
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of substance P-induced liquid secretion across bronchial epithelium

Abstract: The present study was undertaken to identify and determine the mechanism of noncholinergic pathways for the induction of liquid secretion across airway epithelium. Excised porcine bronchi secreted substantial and significant quantities of liquid when exposed to acetylcholine, substance P, or forskolin but not to isoproterenol, norepinephrine, or phenylephrine. Bumetanide, an inhibitor of Na(+)-K(+)-2Cl(-) cotransport, reduced the liquid secretion response to substance P by 69%. Approximately two-thirds of bume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 45 publications
11
70
1
Order By: Relevance
“…In healthy airways the mass of the glands is at least 20-fold greater than the mass of surface goblet cells (Lamb and Reid 1972). Furthermore, when mucus was collected from airways before and after removal of the surface epithelium, there was little difference in the amount collected (Trout, Corboz et al 2001); these results suggest that glands supply ~95% of the mucus that keeps the airways sterile. The importance of airway glands to innate defense has been shown directly by experiments in which ferret tracheal xenografts with glands were much more resistant to infections than those that lacked glands (Dajani, Zhang et al 2005).…”
Section: Airway Mucus and Submucosal Glands Mucusmentioning
confidence: 92%
See 2 more Smart Citations
“…In healthy airways the mass of the glands is at least 20-fold greater than the mass of surface goblet cells (Lamb and Reid 1972). Furthermore, when mucus was collected from airways before and after removal of the surface epithelium, there was little difference in the amount collected (Trout, Corboz et al 2001); these results suggest that glands supply ~95% of the mucus that keeps the airways sterile. The importance of airway glands to innate defense has been shown directly by experiments in which ferret tracheal xenografts with glands were much more resistant to infections than those that lacked glands (Dajani, Zhang et al 2005).…”
Section: Airway Mucus and Submucosal Glands Mucusmentioning
confidence: 92%
“…Glands secrete well in response to VIP, not only glycoconjugates as once thought (Peatfield, Barnes et al 1983), but also fluid (Joo, Irokawa et al 2002;Joo, Saenz et al 2002). They also respond to SP (Coles, Neill et al 1984;Gashi, Borson et al 1986;Shimura, Sasaki et al 1987;Haxhiu, Haxhiu-Poskurica et al 1990;Davis and Tseng 1991;Wagner, Fehmann et al 1995;Trout, Corboz et al 2001), and at low concentrations SP greatly augments the secretory rate produced by VIP (J. Y. Choi, J. P. Ianowski, J. W. Hanrahan, J. J.Wine, unpublished observations). The effect of NO has not yet been tested on single gland secretion, but it does not release glycoconjugates from airway explants (Kim, Okamoto et al 2006), suggesting that its role in gland secretion might be to increase blood flow around the glands in support of fluid transport.…”
Section: Gland Participation In Innate Defensementioning
confidence: 96%
See 1 more Smart Citation
“…The bacteria in CF airways reside in the mucus, which in normal airways is sterile and mobile (6), suggesting that CF mucus is abnormal both in its ability to be cleared from the airways (7) and in its antimicrobial properties (8). Most airway mucus is thought to arise from submucosal glands (9,10), and in the only direct comparisons ever made of airways with and without glands, airways with glands secreted much more lysozyme and were more resistant to bacterial infections, even though no central innervation of the glands was present (11,12). We hypothesize that abnormalities in airway gland mucus, secondary to loss of CFTR-mediated anion secretion, is a significant contributor to airways pathology in CF (13).…”
Section: Introductionmentioning
confidence: 99%
“…It also has a modulatory effect on ovarian function (Pitzel et al 1991). Pigs can be useful models for the study of human cystic fibrosis as it has been shown that substance P induces liquid secretion from bronchial submucosal glands of pigs (Trout et al 2001).…”
mentioning
confidence: 99%